Ethno medicinal knowledge of plants used by irula tribes, nellithurai beat, the Nilgiris, Tamil Nadu, India - Dhivya, SM; Kalaichelvi, K (Asian Journal of Medical Sciences, 2016)
Background: The study of local knowledge about natural resources is becoming increasingly important in defining strategies and actions for conservation. In recent years, work in ethnobotanical knowledge worldwide has increased especially in some parts of Europe, Asia, and Africa. India, a country with a rich culture and traditional knowledge, has contributed a major share of the world’s ethnobotanical work. Aims and Objectives: The main objectives behind this study was to record the plants used for medicinal purposes in Nellithurai Beat through regular field visits because there is no previous reports on the documentation of medicinal plants from Nellithurai Beat, Karmadai Range, Western Ghats, Tamil Nadu, India. Materials and Methods: An ethnomedicinal survey was conducted from January - 2016 to March – 2016. The information on ethnomedicinal uses of plants was obtained through direct field interviews and designed questionnaire. Their vernacular name, family, mode of preparation and medicinal uses were recorded by interviewing the locals of different age groups. Results: During the present study plant species belonging to 36 families were documented. Of the 40 plant species documented 14 were Shrubs,12 Trees, 10 Herbs, 3 Climbers and 1 Epiphyte. Leaves and whole plants are the most widely (50% and 23%) used plant part of the reported medicinal plants and decoction are the most widely (48%) used mode of preparation. Conclusion: The study revealed that tribal community have a great faith in the traditional healing system and they rely on medicinal plants for treatment of various diseases. Due to continuous loss of vegetation, it is necessary that suitability requirements are needed in order to protect the traditional knowledge in a particular area with reference to medicinal plant utilization and the study will be useful for future ethno-pharmacological research for the discovery of new drugs. Asian Journal of Medical Sciences Vol.7(5) 2016 124-128